Identification of the haemolytic activity of Malassezia species - Juntachai W. (2014)
Malassezia species are part of the normal skin flora and are associated with a number of human and animal skin diseases. However, the mechanisms that mediate infection and host-fungal interactions are poorly understood. The haemolytic activity of several microorganisms is considered a factor that contributes to pathogenicity of the organism to humans and animals. This virulence factor was previously identified in several pathogenic fungi that cause systemic mycoses, such as Aspergillus and Candida. In this study, the haemolytic activity of six major Malassezia species, including M. furfur, M. globosa, M. pachydermatis, M. restricta, M. slooffiae and M. sympodialis, was investigated. The haemolytic activity of these species was tested on tryptone soya agar with 5% sheep blood. All the examined Malassezia species produced a halo zone of complete haemolysis. A quantitative analysis of the haemolytic activity was performed by incubating sheep erythrocytes with the extraction from culture of each Malassezia species. Interestingly, M. globosa and M. restricta showed significantly high haemolytic activity compared with the other Malassezia species. In addition, M. globosa also exhibited stable haemolytic activity after treatment at 100 °C and in the presence of some proteases, indicating that this haemolytic factor is different from those of other fungi. © 2013 Blackwell Verlag GmbH.